2010
DOI: 10.1017/s0025315410000317
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and selectivity of the Anomalocardia brasiliana (Mollusca: Veneridae) hand dredge used in southern Brazil

Abstract: In Florianópolis, southern Brazil, the venerid clam Anomalocardia brasiliana has supported subsistence and small-scale commercial fisheries for decades. The introduction of a hand dredge (gancho) since 1987 led to the development of a significant fishery supplying both local and regional shellfish markets. In 1992 one of the main fishing areas in the region was designated as the first Brazilian Marine Extractive Reserve (Pirajubaé RESEX), a federal form of governance intended to promote sustainable exploitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
0
11
0
5
Order By: Relevance
“…3,2 kg de carne/pescador.dia na catação manual efetuada na Reserva de Desenvolvimento Sustentável Ponta do Tubarão, Rio Grande do Norte (Dias et al, 2007) e 210 kg in natura/pescador.dia com o uso da draga empregada na Tapera (Gaspar et al, 2011), não alcançam aqueles obtidos com o gancho na RESEX, com média de 270 kg in natura/pescador.dia. Contribuem para isso a grande abundância do recurso na RESEX (Rosso, 2012) e a elevada eficiência do aparelho que é capaz de remover do sedimento e reter, em uma única passagem sobre o substrato, 69% dos indivíduos com tamanhos superiores ao mínimo legal (Pezzuto et al, 2010).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…3,2 kg de carne/pescador.dia na catação manual efetuada na Reserva de Desenvolvimento Sustentável Ponta do Tubarão, Rio Grande do Norte (Dias et al, 2007) e 210 kg in natura/pescador.dia com o uso da draga empregada na Tapera (Gaspar et al, 2011), não alcançam aqueles obtidos com o gancho na RESEX, com média de 270 kg in natura/pescador.dia. Contribuem para isso a grande abundância do recurso na RESEX (Rosso, 2012) e a elevada eficiência do aparelho que é capaz de remover do sedimento e reter, em uma única passagem sobre o substrato, 69% dos indivíduos com tamanhos superiores ao mínimo legal (Pezzuto et al, 2010).…”
Section: Discussionunclassified
“…Apesar do espaçamento médio constatado em 2005 ter sido ligeiramente inferior ao previsto na legislação (12,4 mm), isso não prejudicou a seletividade da pescaria, visto que praticamente todos os organismos retidos apresentaram comprimento superior ao mínimo estabelecido (20 mm). A elevada eficácia do gancho na seleção do tamanho dos indivíduos retidos já havia sido apontada por Tremel (2001), sendo confirmada durante experimento conduzido por Pezzuto et al (2010), justificando a limitação do espaçamento das grades como medida de gestão na pescaria.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Data from MER Pirajubaé was extracted from literature (von Behr 1995, IBAMA 1996, 2003, Pezzuto and Echternacht 1999, Souza 2007, Pezzuto et al 2010, Vizinho and Tognella-de-Rosa 2010, Spínola 2011). Spínola (2011) was a particularly important source because she discusses in detail fisher participation in Pirajubaé.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the most economically important venerids, and is used as a fishery resource from the French West Indies to Brazil (Moueza et al 1999;Pezzuto et al 2010). Because of its economic importance, the reproductive cycle of A. brasiliana has been investigated by numerous authors at various locations (Narchi 1976;Grotta & Lunetta 1982;Boehs 2000;Araújo 2001;Barreira & Araújo 2005;Lavander et al 2011;Luz & Boehs 2011;Corte et al 2014), and contrasting reproductive patterns have been reported.…”
Section: Introductionmentioning
confidence: 99%